Medical Students' Awareness of Smell Loss as a Predictor for Coronavirus Disease 2019 - Aldrees, Turki; Almatrafi, Sharif; Aldriweesh, Turki; Mokhatrish, Mohammad; Salamh, Abdulaziz; Alkholaiwi, Feras (Frontiers in Public Health, 2020)
Abstract Background: Anosmia has been reported as an early presentation of coronavirus disease 2019 (COVID-19). However, the pathophysiological mechanism of olfactory dysfunction is still unclear. Aim: The aim of this study to evaluate the knowledge regarding common symptoms, anosmia, treatment options and PPE among medical students in three different universities of Saudi Arabia. Methods: This cross-sectional survey conducted among medical students in Saudi Arabia. Google Forms was used to create the survey. The questionnaire included demographic information, knowledge of COVID-19 symptoms, sources of information, and the level of awareness of specific symptoms (loss of smell and taste). Results: A total of 494 students completed the questionnaire. The majority of the participants were aware of common COVID-19 symptoms like fever and cough (79.8% and 67.2%, respectively), but less than half were aware that smell or taste dysfunction might be a symptom of COVID-19 (44.3% and 30.2%, respectively). The present study revealed that the source of information also plays a critical role in medical students’ awareness regarding the symptoms of COVID-19. Students using international organization’s websites, medical databases, or published research had better knowledge of anosmia as a COVID-19 symptom compared to those who used WhatsApp, Google, or unofficial social media pages. In our study, a minority (11.9%) of the participants relied on unofficial social media pages as the main source of their information. Conclusion: Saudi medical students understand that smell or taste dysfunction can be a potential symptom of COVID-19, but this knowledge was not as widespread as the knowledge regarding the most common COVID-19 symptoms.